SUPER LEADERSHIP OF SCHOOL ADMINISTRATORS AS PERCEIVED BY TEACHERS UNDER LOPBURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Pairee , Nutthaya; Hankla , Chalermchai; Chulasukhont, Phuwadon (Journal of Educational Review Faculty of Education in MCU, 2025)
The objectives of this research were 1) to study super leadership of school administrators as perceived by teachers under Lopburi Primary Educational Service Area Office 1 and 2) to compare teachers’ perceptions of super leadership based on their educational qualifications, work experience, and school size. The sample were 300 teachers from Lopburi Primary Educational Service Area Office 1 in the 2024 academic year, using stratified random sampling. The research instrument was a questionnaire with a reliability coefficient of 0.992 Data was analyzed to find percentage, mean, standard deviation, t-test, and one-way analysis of variance (ANOVA). The research findings were as followed: 1) Super leadership of school administrators as perceived by teachers under Lopburi Primary Educational Service Area Office 1, was found to be at a high level both overall and all dimensions. 2) A comparative analysis super leadership of school administrators as perceived by teachers under Lopburi Primary Educational Service Area Office 1 qualifications revealed statistically significant differences at the 0.05 level. However, when categorized by professional experience and school size were not different.